2017
DOI: 10.1038/s41467-017-00612-6
|View full text |Cite
|
Sign up to set email alerts
|

NFATc1 controls the cytotoxicity of CD8+ T cells

Abstract: Cytotoxic T lymphocytes are effector CD8+ T cells that eradicate infected and malignant cells. Here we show that the transcription factor NFATc1 controls the cytotoxicity of mouse cytotoxic T lymphocytes. Activation of Nfatc1 −/− cytotoxic T lymphocytes showed a defective cytoskeleton organization and recruitment of cytosolic organelles to immunological synapses. These cells have reduced cytotoxicity against tumor cells, and mice with NFATc1-deficient T cells are defective in controlling Listeria infection. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
139
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 162 publications
(159 citation statements)
references
References 70 publications
(86 reference statements)
14
139
0
2
Order By: Relevance
“…Analysis of DNase I hypersensitivity (Bevington et al, 2016) and ATAC-sequencing (Mognol et al, 2017) data from naïve and activated CD8 + T cells revealed open chromatin regions in the regulatory regions of Irf4, Slc2a3 (Figure 5A) as well as Hif1a, Myc, Slc2a1 and Hk2 (Figure S5A). To determine if NFAT binds to these open chromatin regions, we analyzed genome-wide ChIP-sequencing (ChIP-seq) data that report on the binding of NFATc2 in WT (and Nfatc2 -deficient) CD8 + T cells (Martinez et al, 2015) and NFATc1 in activated CD8 + T cells from a NFATc1 BAC-transgenic mouse line (Klein-Hessling, 2017). We found strong binding of both NFATc1 and NFATc2 within open chromatin regions in the promoters of Irf4 and Hif1a as well as in regulatory elements downstream of the Irf4 gene (Figure 5A and S5A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of DNase I hypersensitivity (Bevington et al, 2016) and ATAC-sequencing (Mognol et al, 2017) data from naïve and activated CD8 + T cells revealed open chromatin regions in the regulatory regions of Irf4, Slc2a3 (Figure 5A) as well as Hif1a, Myc, Slc2a1 and Hk2 (Figure S5A). To determine if NFAT binds to these open chromatin regions, we analyzed genome-wide ChIP-sequencing (ChIP-seq) data that report on the binding of NFATc2 in WT (and Nfatc2 -deficient) CD8 + T cells (Martinez et al, 2015) and NFATc1 in activated CD8 + T cells from a NFATc1 BAC-transgenic mouse line (Klein-Hessling, 2017). We found strong binding of both NFATc1 and NFATc2 within open chromatin regions in the promoters of Irf4 and Hif1a as well as in regulatory elements downstream of the Irf4 gene (Figure 5A and S5A).…”
Section: Resultsmentioning
confidence: 99%
“…NFATc2 ChIP-seq data (Martinez et al, 2015) and genome-wide NFATc1 chromatin binding data (using T cells from a BAC-transgenic mouse strain in which NFATc1 is endogenously biotinylated by the biotin-ligase BirA and precipitated using streptavidin beads) (Klein-Hessling, 2017) were aligned to open chromatin regions defined by DNase I hypersensitivity sites in naïve and CD8 + T cell blasts (Bevington et al, 2016) and accessible chromatin regions defined by ATAC-seq in resting and PMA/ionomycin-stimulated CD8 + T cells (Mognol et al, 2017). All sequencing data was mapped to the mouse mm9 genome assembly using the Bowtie software package.…”
Section: Star Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon T cell activation, nuclear NFAT proteins complex with AP1 transcription factors to stimulate gene expression linked to activation. NFATc1, in particular, is necessary for cytotoxic CD8+ T cell activation, by regulating effector memory T cell expansion and gene expression associated with cytotoxicity . CD8+ T cells that lack NFAT have severely impaired cytotoxicity against A20J tumor cells and Listeria infection .…”
Section: Discussionmentioning
confidence: 99%
“…NFATc1, in particular, is necessary for cytotoxic CD8+ T cell activation, by regulating effector memory T cell expansion and gene expression associated with cytotoxicity . CD8+ T cells that lack NFAT have severely impaired cytotoxicity against A20J tumor cells and Listeria infection . Indeed, low NFAT expression correlates with poor prognosis in non‐small cell lung cancer .…”
Section: Discussionmentioning
confidence: 99%